2023
DOI: 10.1007/s10071-023-01780-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectric networks: the cognitive glue enabling evolutionary scaling from physiology to mind

Abstract: Each of us made the remarkable journey from mere matter to mind: starting life as a quiescent oocyte (“just chemistry and physics”), and slowly, gradually, becoming an adult human with complex metacognitive processes, hopes, and dreams. In addition, even though we feel ourselves to be a unified, single Self, distinct from the emergent dynamics of termite mounds and other swarms, the reality is that all intelligence is collective intelligence: each of us consists of a huge number of cells working together to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 193 publications
0
12
0
Order By: Relevance
“…Specifically, we have argued that regulative morphogenesis is a kind of behavior of cellular collectives traversing anatomical morphospace (Fig. 1f, g) [27][28][29][30][31][32] , and others have argued that immune systems 33,34 , bacterial biofilms [35][36][37][38] , and many other unconventional substrates [39][40][41][42] can be effectively understood and rationally controlled by using techniques from behavioral and cognitive science 43 .…”
mentioning
confidence: 99%
“…Specifically, we have argued that regulative morphogenesis is a kind of behavior of cellular collectives traversing anatomical morphospace (Fig. 1f, g) [27][28][29][30][31][32] , and others have argued that immune systems 33,34 , bacterial biofilms [35][36][37][38] , and many other unconventional substrates [39][40][41][42] can be effectively understood and rationally controlled by using techniques from behavioral and cognitive science 43 .…”
mentioning
confidence: 99%
“…▪ Levin (2023a , 2023b) equally and empirically demonstrates goals and the Bayesian priors of associative learning from these goals as much more fundamentally stored among every organism than purely among the centralized nervous system.…”
Section: Key Conceptsmentioning
confidence: 88%
“…o These multilevel competencies (and subsequent goals) begin at the most fundamental levels of biology ( Levin, 2023a , 2023b ).…”
Section: Key Conceptsmentioning
confidence: 99%
“…In this view, the causes of collapse can be different in different individuals, but lead to the same outcome (i.e., the onset of the hallmarks of ageing). Recently, it has also been suggested that bioelectric networks act as body coordinators, modulating communications between cells and tissue ( Levin, 2023 ). Ageing would then begin following the miscoordination of such signals, leading to divergence and aberrancies in tissue and organ behaviours ( Pio-Lopez and Levin, 2024 ).…”
Section: Discussionmentioning
confidence: 99%